An effective way to hydrophilize gigaporous polystyrene microspheres as rapid chromatographic separation media for proteins - Qu, Jian-Bo (Langmuir : the ACS journal of surfaces and colloids, 2008)
To overcome the disadvantages of protein denaturation and nonspecific adsorption on poly(styrene-divinylbenzene) (PS) medium as a chromatographic support, gigaporous PS microspheres prepared in our previous study were coated with hydrophobically modified agarose (phenoxyl agarose, Agap). Both the modification of agarose and the gigaporous structure of PS microspheres provided an advantage that facilitated the coating of Agap onto PS microspheres. The amount of Agap adsorbed onto the PS surface was examined as a function of the polymer concentration, and various samples of microspheres, differing in surface Agap density, were prepared. The adsorbed layer was then stabilized by chemical cross-linking and its stability was evaluated in the presence of sodium dodecyl sulfate. Results showed that PS microspheres were successfully coated with Agap, while the gigaporous structure could be well maintained. After coating, the nonspecific adsorption of proteins on PS microspheres was greatly reduced. Flow hydrodynamics experiments showed that the Agap-co-PS column had low backpressure, good permeability, and mechanical stability. Such a procedure could provide a hydrophilic low-pressure liquid chromatographic support for different types of chromatography, since the Agap layer may be easily derivatized by classical methods, and because of their good permeability, the coated microspheres have great potential applications in high-speed protein chromatography